SPANISH VERB SUPPORT CONSTRUCTIONS FROM A LEARNER PERSPECTIVE - Buckingham, Louisa (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Few studies exist on verb-support constructions (VSC) from a didactic perspective; however, the scant evidence available suggests that learners tend to employ these structures less frequently than native speakers. Didactic materials and dictionaries provide only very superficial treatment of these collocations. This corpus-based study of VSC in Spanish identifies a group of typical items for a specific genre (social sciences), and then describes certain morphosyntactic and semantic challenges that the extracted corpus examples present to English and German-speaking learners.Using these same concordances, we then develop model didactic exercises to focus on form, meaning and use. Resumen Pocos estudios existen sobre las construcciones con verbo soporte (CVS) desde una perspectiva didáctica. No obstante, la poca evidencia a nuestro alcance indica que los aprendices emplean estas estructuras con una frecuencia menor comparada con los hablantes nativos. Los recursos didácticos y los diccionarios proporcionan únicamente un tratamiento superficial de estas colocaciones. Este estudio de corpus de las CVS en español tiene como objetivo identificar los ítems más típicos para un registro particular (las ciencias sociales) y describir las dificultades morfosintácticas y semánticas que los ejemplos extraídos presentan a los aprendices de habla inglesa y alemana. Utilizando las mismas concordancias, desarrollamos ejercicios didácticos que enfocan las formas, el sentido y el uso.